Lingual Nerve Entrapment in Fused Submandibular and Sublingual Salivary Glands: A Unique Finding. Issue 7 (October 2018) - Nayak, Satheesha B.; Kumar, Naveen
Abstract : Abstract: Lingual nerve (LN) is one among the 3 branches of posterior division of mandibular nerve. It might get entrapped in the infratemporal fossa by lateral pterygoid muscle, pterygospinous ligament, or lateral pterygoid plate. Its entrapment in the submandibular region has not been reported yet. A unique entrapment of LN in the fused submandibular and sublingual salivary glands in a cadaver was reported. The deep parts of the submandibular and sublingual salivary glands were completely fused with each other. The LN passed through the center of the fused part. Histologically both submandibular and sublingual salivary glands had both mucous and serous acini. Though this entrapment might not cause any functional problems, it might get injured during various surgical procedures of the submandibular region.